If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7x + -3) + 4 = 40 Reorder the terms: 2(-3 + 7x) + 4 = 40 (-3 * 2 + 7x * 2) + 4 = 40 (-6 + 14x) + 4 = 40 Reorder the terms: -6 + 4 + 14x = 40 Combine like terms: -6 + 4 = -2 -2 + 14x = 40 Solving -2 + 14x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 14x = 40 + 2 Combine like terms: -2 + 2 = 0 0 + 14x = 40 + 2 14x = 40 + 2 Combine like terms: 40 + 2 = 42 14x = 42 Divide each side by '14'. x = 3 Simplifying x = 3
| 14y+8=-5y+4 | | (-11a-8b)(-5a-6b)= | | -2x+15=9 | | -8-23=-15 | | 4.8x-4=3.8x | | 5x-(2x+6)=15 | | .34(y+3)=4y | | (9c-2d)(3c-7d)= | | y+3=12y | | 5v^2-19v=4 | | (6x-y)(4x+3y)= | | n^2+5=-6n | | y^2-24x+144=0 | | 2x-11=-7 | | 2a+4b+-2a+-b= | | (-z+2.1)(3z+3)= | | .50-x+1.5=x-4 | | 6x+32=80 | | (12c+5)(-6c-2)= | | 3+y=10(y+1) | | 2x-(5x-6)=-10 | | (7y-10)(2y-11)= | | (-6b+9)(8b-1)= | | (-2a-1)(-4a-8)= | | 9-3(y-1)=20 | | 3=n+13 | | 4y-4=10y+15 | | -7+5(n-4)=1 | | 4x-1=5x+3 | | 6w-125=35 | | 2x^2+-5x=20 | | 8.25y+3.5=36.5 |